GAP Analysis Between The Problems And Policy On Licensing Of Batik Waste Management With Field Practices In The Batik Industry In Pekalongan - Brian Tri Hutomo; Tiara Putri Setia; Mutasim Bilah; Sami’an (Jurnal Multidisiplin Sahombu, 2025)
Numerous batik producers have yet to effectively manage the trash generated from batik production. Batik waste is classified as toxic and hazardous waste, which is hazardous if not properly treated prior to being released into the river. Direct release of batik waste into the river might adversely affect the neighboring community and the aquatic biota. Article 11, paragraph (1) of Pekalongan City Regional Regulation Number 12 of 2014 stipulates that any individual or corporate organization generating garbage is obligated to manage the waste they produce. This study seeks to identify the disparity between governmental policy on biodegradable waste management and the actual practices observed in the field. The author use a qualitative research methodology, specifically a qualitative technique, to gain an in-depth understanding by gathering data through interviews, observations, and document analysis, while directly assessing the conditions in the field. The author interviewed batik producers and government officials to identify discrepancies in the management of batik waste between the two parties, and also directly observed that numerous rivers were contaminated by batik waste. The government has established a Wastewater Treatment Plant (IPAL) to process batik wastewater prior to its discharge into the river; however, not all regions with numerous batik manufacturers own IPALs due to financial constraints. The government is eager to assist producers in managing their batik waste. If there is no wastewater treatment facility (IPAL) in their production region, Pekalongan Environmental Agency is prepared to collect their batik trash and transport it to the nearest IPAL for processing.